The Influence Of Organizational Climate And Leadership On The Performance Of Sekolah Menengah Atas Cinta Budaya Teachers - Edward A. Lbn. Raja*; Rozaini Rozaini; Rita Kartika Dongoran; Adiwima Zebua; Endang D. Sinaga (Riwayat: Educational Journal of History and Humanities, 2024)
Knowledge is the basic need of every individual. Because of the importance of education, the government requires education for at least 9 years and it is recommended that more than that The formulation of the problem in this study is as follows: "Is there any influence of organizational climate and leadership on teacher performance at Sekolah Menengah Atas Cinta Budaya Medan. In an organization, the role of a leader is very large in creating organizational work productivity, where the leader can create a good working atmosphere. Then a good organizational climate will influence good working conditions where there is a conducive working atmosphere in the organization which can be seen from the performance of each employee in the organization who helps each other in their work. The results of this research explain that there is an influence between organizational climate and leadership in influencing performance at Love Culture High School. Simultaneous test results show that the independent (free) variables studied simultaneously have a significant effect on the dependent (bound) variables. This means that the variables of Organizational Climate and Principal Leadership have a significant effect on teacher performance at Sekolah Menengah Atas Cinta Budaya Medan. The coefficient value of each variable is 0.076 for X1, and 0.672 for X2. The test results partially show that the variables of Organizational Climate and Principal Leadership have no effect on Teacher Performance at Sekolah Menengah Atas Cinta Budaya Medan. This means that separately the Organizational Climate and the Principal's Leadership have no influence on the teacher's performance at Sekolah Menengah Atas Cinta Budaya Medan. The research results explain that there is an influence between organizational climate and leadership in creating performance at Sekolah Menengah Atas Cinta Budaya Medan.